Seismic Assessment of RC Frame Under Amalgamation of Different Bracings - Rishiv Virdhi, Jagdish chand (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
A number of studies was performed on the structures with various structural configuration and a variety of studies are still being carried out in finding the response spectrum of different amalgamation of bracings and shear walls. The response spectrum method was used to find the effect of the combination of various bracings on the different seismic factors like overturning moment, maximum storey drift, story displacement and storey shear. As the use of the shear walls is most common but the cost of installing the shear wall is very high so in this analytical study the effect of the steel bracings with different combinations on the multi-storey building was examined and the best suitable combination was found out of it.